Cutting-Edge Developments in Oncology Research - Datta, Neelabh (Indian Journal of Medical and Paediatric Oncology, 2022)
The field of oncology research has made many successful advances, and new discoveries have started making headlines. As an example, the identification of immune checkpoint inhibition mechanisms in carcinogenic cells led to the development of immunoassays, which have helped many cancer convalescents recover. This article covers the most advanced cutting-edge areas of cancer research: exosomes, microbiomes, immunotherapy, nanocarriers, and organoids. Research on exosomes advances cancer detection and treatment modalities, as well as further understanding of mechanisms that regulate carcinogen cell division, proliferation, invasion, and metastasis. Microbiome consents the researchers to understand the disease cancer. Immunotherapy is the third method in the treatment of cancer. Organoid biology will be further expanded with the aim of translating research into customized therapeutic therapies. Nanocarriers enable cancer specific drug delivery by inherent unreceptive targeting phenomena and implemented active targeting strategies. These areas of research may also bring about the advent of the latest cancer treatments in the future. Malignant infections are one of the leading grounds for demise in the society. Patients are treated with surgery, radiation, and chemotherapy. In chemotherapy, the malignant cells are destroyed and the tumor burden is reduced. However, in most cases, resistance to chemotherapy develops. Therefore, there is a constant need for new additional treatment modalities and chemotherapeutic complex rules. Due to the rapid development in cancer research, I can only mention a few goals and treatment options that I have chosen; However, this review specializes in new and admirable significant strategies and compounds.
Keywords: cancer treatment; chemotherapy; exosome; immune checkpoint; immunotherapy; medical oncology; microbiome; nanocarriers; oncology; organoid